Debt management for development protection of the poor and the millennium development goals - Raffer, Kunibert 1951- (Edward Elgar, 2010)
"T̀he problem of the debt burden and pleas for debt relief have been compared to the girl who killed both her parents and then pleaded for mercy on the grounds that she was an orphan. (It has been called the classic definition of chutzpah.) Kunibert Raffer has more sympathy for the debtors. He discusses the international debt problem in a profound way and his proposal, the Raffer proposal, is ingenious, practical and wise.'--Paul Streeten, Boston University, USA" "K̀unibert Raffer, a distinguished academic, has never confined himself to an ivory tower. Instead he has consistently used his extensive knowledge of law, history, economics and politics to argue for an end to the structural injustice of relationships between rich creditor countries and poor debtor nations. I have always admired the man and his work, and believe the ideas outlined in this book are vital if justice is to be the basis of international financial relations.'--Ann Pettifor, New Economics Foundation and Advocacy International" "This book exposes intolerable global double standards in the treatment of debtors and argues that fairness, economic efficiency and principles common to all civilized legal systems, must and can be applied to so-called d̀eveloping countries', or Southern sovereign debtors.".